Studi Kualitatif Tentang Pengaruh Pengawak Ranpur Tank BMP 3f dan Kesiapan Materiel Tank BMP 3 dalam Meningkatkan Efektivitas Pelaksanaan Latihan Pendaratan Amfibi - Arifin Parmonangan Manalu; Rudy Sumanwtri; Muh Ilham (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to analyze the influence of the competence of BMP 3F armored vehicle operators and the operational readiness of BMP 3F material on the effectiveness of amphibious landing training conducted by the 2nd Amphibious Tank Battalion of the Marine Corps in Surabaya. Using a descriptive qualitative approach, this research explores two main variables: operator competence and material readiness, and how both factors contribute to the success of the training. Data was collected through in-depth interviews with armored vehicle operators, logistics personnel, and commanders, as well as observations of the training execution. The results show that high operator competence, both in technical skills and work attitude, plays a significant role in the success of the training. Additionally, optimal material readiness, including routine maintenance and efficient logistical support, also has a major impact on the smooth execution of the training. These two variables interact simultaneously and cannot be separated, highlighting the importance of integrating human resource development and equipment readiness to achieve training effectiveness. This study is expected to contribute practical insights into the planning and execution of more effective military training, as well as improve the operational readiness of units.